Time Unit Interactive Ebook to Improve Logical Thinking Skills for Grade 2 Elementary School Students - Arsita Wahyuningsih; Nurdyansyah Nurdyansyah (Universitas Muhammadiyah Sidoarjo, 2023)
This research is motivated by problems that occur in the learning outcomes of second grade students at Muhammadiyah 1 Elementary School Candi. The objectives of this study include: 1) To analyze the feasibility of interactive ebooks on time units in improving logical thinking skills of second grade students at Muhammadiyah 1 Elementary School Candi, 2) To analyze the effectiveness of interactive ebooks on time units in improving logical thinking skills of second grade students at Muhammadiyah 1 Elementary School Candi. The type of research used is the type of research and development or called Research and Development with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The product produced in this research is an interactive ebook of time unit material for class II elementary school. The result of this development research is that the interactive ebook has very good quality with the results of the validity of material experts at 96.15%, design experts at 96.05% and linguists at 90%. From the score obtained, it can be said that the interactive ebook on time unit material is very feasible to be applied at Muhammadiyah 1 Elementary School Candi and can improve students logical thinking skills.